Layer-by-layer reduced graphene oxide (rGO)/gold nanosheets (AuNSs) hybrid films: significantly enhanced photothermal transition effect compared with rGO or AuNSs films1. Issue 71 (2nd August 2015) - Nie, Kun; An, Qi; Tao, Shengyang; Zhang, Zepeng; Luan, Xinglong; Zhang, Qian; Zhang, Yihe
<x xml:space="preserve">Abstract</x> The photothermal effects of layer-by-layer AuNS (gold nanosheets)/rGO hybrid films outperformed that of rGO or AuNSs films under NIR irradiation.